Analisis Impulse Buying Mahasiswa Pada Flash Sale dan Gratis Ongkir Shopee: Keinginan atau Kebutuhan? - Dede Rohman; Ira Triana; Noviana Ayu Lestari; Rayona Hanita; Rama Wijaya Abdul Rozak; Heni Mulyani (Jurnal Ecogen, 2023)
Provide new insights into the factors that influence impulse buying behavior and raise awareness about good financial management and make important contributions in the development of policies that can protect consumers, especially students from unwanted financial risks among students. Using descriptive qualitative methods with a focus on questionnaires distributed online through several platforms as a data collection tool which is then processed through three stages, namely data tabulation, description and analysis, and discussion. Flash sales and free shipping vouchers have a significant impact in motivating students to shop at Shopee and can be an important factor in influencing consumer purchasing decisions.